Síntese de carbono micro-mesoporoso ordenado via nanocasting a partir de óleo de dendê residual e o seu potencial de adsorção para corantes reativos em soluções aquosas - Lima Sobrinho, Raimundo Alves (2018)
Population growth, industrial and agricultural activities produce daily considerable amounts of wastewaters containing numerous organic pollutants (organic dyes, benzene, toluene, ethylbenzene and xylene), which are thrown directly into the environment, causing health effects to humans as well as aquatic beings. Dyes are widely used in several industrial segments including cosmetics, leather, printing, paper, food and textile, being considered hazardous pollutants due to high chemical stability in aqueous medium, possessing also no biodegradable nature making their removal difficult. Among the number of methods employed for the treatment of aqueous effluents, adsorption has been considered one of the most promising ones owing to the high efficacy, convenience and feasibility. Activated carbon is certainly the most used adsorbent owing to physical properties (high surface area and porosity) as well as surface chemistry. However, activated carbons are usually inefficient to remove high molecular weight molecules such as dyes, owing to the microporous structure. Thus, a novel type of micro-mesoporous carbon has been synthesized in the work employing a mechanosynthesized silica template (HZSM-5/SBA-15) in variable mass proportions, as well as palm oil cooking waste as carbon source. Materials were characterized by X-ray diffraction (XRD), N2 adsorption-desorption isotherms using BET model, Fourier-transform infrared spectroscopy, scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM) and zeta potential determination. Scanning electron microscopy images showed the efficiency of the mechanosynthesis to all mass proportions used, while the textural properties were strongly influenced by the presence of SBA-15. X-ray diffraction patterns for ordered mesoporous carbons (OMC’s) confirmed the mantainance of the crystalline order typical of the templates. The resulting mesoporous carbon has been evaluated as adsorbent to different dye molecules, including molecules with distinct sizes and electrical charges. Results revealed that the carbon adsorbent exhibited high affinity for cationic dyes owing to the presence of negatively charged functional groups onto the surface and also that the mesoporous structure favors high diffusion rates leading to a higher adsorption efficiency compared to the other adsorbents studied (activated carbon, SBA-15, SBA-15/HZSM-5-50, OMC-NC).